Digitalization in The Hospitality Industry: Trends That Might Shape The Next Stay Of Guests - Kudratov Samat Sharofboy ugli (Universitas Muhammadiyah Sidoarjo, 2022)
The digital technology for guests means an easy life, and accordingly to that, our appetite for this lifestyle is insatiable. With each new application or connected device, the digital technology shows us that everything is possible, and one sector in which this transformation is increasingly apparent is the hospitality one, where everything from the check-in process to in-room technology options is rapidly changing, therefore this means constant changes in the behavior of their guests. Nowadays, as automation and digitization continue to proliferate, and guests become increasingly tech-savvy, in response to this movement, touch points across the hospitality industry are embracing new digital trends and smart technology to make the customer journey as seamless and enjoyable. Key words: hotel, hospitality, guests, digital, digitalization, technology